A educação como direito social e exercício da cidadania: um estudo sobre o processo da redemocratização brasileira (1985 a 2015) - Barreto, Ana Cristina Carvalho Sá (2015)
The present work has as title education as social right and exercise of citizenship: a study on the Brazilian re-democratization process (1985 to 2015) and problematizes the issue regarding the need for professor/student critical awareness to recognize their rights to education and fight for their better effectuation. The discussion of teacher formation will reference the emancipatory pedagogy of Paulo Freire. We understand that his dialogic perspective is one of the main postulates to promote awareness of the educator and make him a subject. Another reference we anchor this research on is educator Dermeval Saviani, whose education proposal is theoretical-critical and an important reference to understand the Brazilian educational system. The methodology used will be a qualitative approach using the exploratory technique and focuses on conducting a documental analysis of sanctioned laws regarding education. We hope this work contributes in the dissemination of a more critical and aware education for the effective exercise of citizenship.